(untitled) (Annals of Medical Research, 2021)
Aim: Etiology of non-alcoholic fatty liver disease is not exactly understood. The aim of this study is to investigate the etiologic factors in patients with non-alcoholic fatty liver disease in and around Malatya, Turkey.